(untitled) (Canadian Diabetes & Endocrinology Today, 2026)
Perimenopause is a clinically defined reproductive transition characterized by menstrual-cycle variability, fluctuating ovarian hormone secretion, and symptoms that often overlap with endocrine disease. Endocrinologists are well positioned to distinguish physiological reproductive aging from thyroid disease, hyperprolactinemia, pregnancy, premature ovarian insufficiency, and other causes of oligo-amenorrhea; to identify abnormal uterine bleeding requiring gynecologic evaluation; and to address the concurrent emergence of cardiometabolic and skeletal risk. Management should be symptom-directed and should explicitly separate the need for contraception and cycle control from the use of menopausal hormone therapy. This review presents a practical, evidence-based approach to diagnosis, risk assessment, and treatment for the endocrinology setting.